Ustadz Alfie Alfandy's Digital-Based Preaching Strategy For Generation Z Through Youtube - Akbar Satria; Nase Saepudin Zuhri; Encep Taufik Rahman; Muhamad Rizza (Hikmah, 2026)
This study examines the digital-based khitobah strategy employed by Ustadz Alfie Alfandy in reaching Generation Z audiences through YouTube. The rapid development of digital media has transformed Islamic communication practices, particularly among younger audiences who prefer interactive, visual, and emotionally engaging content. This research uses a qualitative descriptive approach with a case study method. Data were collected through observation of selected YouTube content, documentation, and a literature review on digital da’wah and Islamic communication. The findings show that the effectiveness of Alfie Alfandy’s strategy lies in the integration of casual language, storytelling, empathy, and authentic self-representation. His communication style reduces social distance between the preacher and the audience, making religious messages more relatable to Generation Z. In addition, audience segmentation focusing on biker communities, street youth, and marginalized groups strengthens the inclusiveness of his preaching. The integration of online preaching and offline community activities also reinforces long-term engagement and behavioral transformation. This study concludes that adaptive and narrative-based communication strategies significantly enhance the effectiveness of digital khitobah in contemporary Islamic broadcasting.